1999
DOI: 10.1088/0953-8984/11/1/003
|View full text |Cite
|
Sign up to set email alerts
|

O-mediated layer growth of Cu on Ru(0001)

Abstract: The film growth of Cu on clean and O-precovered Ru(0001) at different growth temperatures form 300 K to 450 K was investigated by scanning tunnelling microscopy (STM). Cu films on clean Ru(0001) grow in a multilayer mode at these temperatures. By using an O precoverage in the range of 0.1 monolayers (ML) up to a saturation coverage of 0.5 ML on clean Ru(0001), at 400 K different growth regimes are obtained. For ML a multilayer mode is preserved which changes into an O-induced two-dimensional (2D) growth for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…AES [363], ICISS [242], work function measurements [198,364] and STM observations [241,365] have revealed that oxygen atom is always present on the surface of the grown Cu films deposited on an oxygen pre-covered Ru(0001) surface. Under certain conditions (Y O =0.2-0.4 ML, T $ 400 K), the work function, monitored during film deposition, oscillates with a period of one monolayer of copper epitaxial growth.…”
Section: Bond Switching: O-floating and O-diffusingmentioning
confidence: 99%
See 3 more Smart Citations
“…AES [363], ICISS [242], work function measurements [198,364] and STM observations [241,365] have revealed that oxygen atom is always present on the surface of the grown Cu films deposited on an oxygen pre-covered Ru(0001) surface. Under certain conditions (Y O =0.2-0.4 ML, T $ 400 K), the work function, monitored during film deposition, oscillates with a period of one monolayer of copper epitaxial growth.…”
Section: Bond Switching: O-floating and O-diffusingmentioning
confidence: 99%
“…If the tetrahedron is destroyed, oxygen will seek new partners for a new tetrahedron-a process of re-bonding or bond switching. This may provide a mechanism for O-penetrating in bulk oxidation and O-floating in the epitaxial growth of metals on the oxygen pre-covered metal surfaces [241,242].…”
Section: ð3:2:2bþmentioning
confidence: 99%
See 2 more Smart Citations
“…AES [3], ICISS [4], work function measurements [5,6], and STM observations [7,8] revealed that oxygen atom is always present on the surface of the grown Cu films deposited on an oxygen pre-covered Ru(0001) surface. Under certain conditions (H O = 0.2-0.4 ML, T * 400 K), the work function, monitored during film deposition, oscillates with a period of one monolayer of copper epitaxial growth.…”
Section: Bond Switching: O-floating and O-diffusingmentioning
confidence: 98%